2020
DOI: 10.4162/nrp.2020.14.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Hypotriglyceridemic effects of brown seaweed consumption via regulation of bile acid excretion and hepatic lipogenesis in high fat diet-induced obese mice

Abstract: BACKGROUND/OBJECTIVES: The present study aimed to further investigate the potential health beneficial effects of long-term seaweed supplementation on lipid metabolism and hepatic functions in DIO mice. MATERIALS/METHODS: Four brown seaweeds (Undaria pinnatifida [UP], Laminaria japonica [LJ], Sargassum fulvellum [SF], or Hizikia fusiforme [HF]) were added to a high fat diet (HFD) at a 5% ratio and supplemented to C57BL/6N mice for 16 weeks. Triglycerides (TGs) and total cholesterol (TC) in the liver, feces, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Han et al reported that LJP exerted a hypotriglyceridemic effect on HFD-fed mice by phosphorylating 5 AMP-activated protein kinase [ 31 ]. LJP was supplemented with 5% of the diet during the 16-week experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al reported that LJP exerted a hypotriglyceridemic effect on HFD-fed mice by phosphorylating 5 AMP-activated protein kinase [ 31 ]. LJP was supplemented with 5% of the diet during the 16-week experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to fucoidan and iodine, alginates, polyphenols, and polysaccharides as bioactive nutritional compounds extracted from LJP have been evaluated as solutions for the treatment and prevention of Met-related diseases [ 81 ]. In this review, alginates, polyphenols and polysaccharides have been reported to possess anti-diabetic [ 3 , 10 , 19 , 24 , 33 ], anti-obesity [ 29 , 30 , 31 , 32 , 38 ], antioxidant [ 15 , 34 , 37 ], anti-inflammatory [ 37 , 38 ], and hypolipidemic [ 15 , 33 , 34 , 37 ] effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are reports about the mechanism of S. fusiforme inhibiting symptoms of diabetes. , In Wei’s research, five polysaccharides extracted from S. fusiforme , and their influences on fasting hypoglycemia and intestinal flora imbalance caused by high-fat diet (HFD) were investigated . The studies showed that C57BL/6J male mice fed HFD for 4 weeks had severe hypoglycemia.…”
Section: Bioactivities Of S Fusiformementioning
confidence: 99%